Religion, caste and access to credit by SMEs: Is there a link? - Saibal Ghosh (Cogent Economics & Finance, 2023)
Using unit-level data on the entire population of registered manufacturing SMEs in 2007 for India, we explore the impact of religiosity on their access to finance. The findings indicate that certain categories of religion, such as Hindus and Sikhs, are less likely to have access to institutional credit, after accounting for other relevant factors. The disaggregated analysis suggests that these results differ across key characteristics such as SME ownership and gender and caste. In addition, the results also show SMEs for the aforesaid religious categories are less likely to use institutional credit. Therefore, our findings underscore the role and relevance of religion in influencing SMEs access to credit for a large emerging economy whose religious demography differs significantly from Western democracies.
Keywords: G21; Z12; 330; finance; India; religiosity; SME